The Impact of Intrusive Rumination on College Students’ Creativity During the COVID-19 Pandemic: The Mediating Effect of Post-traumatic Growth and the Moderating Role of Psychological Resilience - Xu, Yanhua; Wu, Jiamin; Li, Qian; Zeng, Wei; Wu, Chujin; Yang, Yuhao; Chen, Zhihao; Xu, Ziying (Frontiers in Psychology, 2022)
Purpose: The researchers constructed a mediated regulation model to examine the effects of intrusive rumination on the creativity of college students during the COVID-19 pandemic, as well as the mediating effect of post-traumatic growth and the moderating role of psychological resilience. Methods: A sample of 475 university students from Guangdong Province, China, were surveyed with the Runco Ideational Behavior Scale, the Event Related Rumination Inventory, the Posttraumatic Growth Inventory, and the Psychological Resilience Scale SPSS (version 23) and PROCESS (version 3.3) were used for correlation analysis, mediation analysis, and mediated moderation analysis. Results: (1) Intrusive rumination was positively correlated with post-traumatic growth and creativity but negatively correlated with psychological resilience. Psychological resilience was positively correlated with post-traumatic growth and creativity. Post-traumatic growth and creativity were positively correlated. (2) Post-traumatic growth played a mediating role in the relationship between intrusive rumination and creativity. (3) Psychological resilience moderated the first half of the pathway “intrusive rumination → post-traumatic growth → creativity.” Conclusions: Intrusive rumination affected creativity directly and also indirectly through post-traumatic growth. At the same time, psychological resilience played a moderating role between intrusive rumination and creativity. The correlation between intrusive rumination and post-traumatic growth was stronger when levels of psychological resilience levels were higher.